Constructing Moral Meaning in Ziad Doueiri’s the Insult: A Roland Barthes Semiotic Study - Cut Zulfa Zainurrohmah; Setia Gumilar; Muhammad Nurhasan; Akmaliyah Akmaliyah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study addresses the problem of how moral messages are constructed and communicated in films that portray socio-political conflict within plural societies, particularly in contexts shaped by historical trauma and sectarian division. Focusing on Qadiyya Raqm 23 (The Insult), directed by Ziad Doueiri, the study aims to uncover the moral meanings embedded in the film and to explain how cinematic signs function as vehicles of ethical discourse. Methodologically, the research adopts a qualitative descriptive approach grounded in Roland Barthes’ semiotic framework, emphasizing the levels of denotation, connotation, and myth. Key scenes, dialogues, and visual symbols are analyzed to identify patterns of meaning and ideological representation. The results reveal that the film represents personal conflict as a symbolic extension of collective memory, identity politics, and unresolved historical grievances in Lebanese society. At the denotative level, the narrative depicts a legal dispute between two individuals, while at the connotative level it exposes deep-seated emotions of humiliation, pride, and resentment. At the mythic level, the film constructs a broader moral discourse that critiques inherited hatred, sectarian prejudice, and social discrimination, while emphasizing human dignity, empathy, and the necessity of reconciliation. This study contributes to film and cultural studies by demonstrating the relevance of Barthesian semiotics in decoding moral narratives in Middle Eastern cinema. It also offers insight into how film can function as a reflective medium for promoting ethical awareness and social coexistence in plural and post-conflict societies.